RETRACTED: Internal control of settlements with personnel on remuneration in the management system of organizations - Zakirova Alsou; Klychova Guzaliya; Alexandrova Elena; Selezneva Irina; Gorbushina Natalia; Bekesheva Dana (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001